Investigation the Effects of Lactobacillus acidophilus and Lacto-bacillus casei on aflR Gene expression in Aspergillus parasiticus by Real Time-PCR - Farzaneh NATEGHI; Fatemeh NOORBAKHSH; Ensieh LOTFALI; Sassan REZAIE (Tehran University of Medical Sciences, 2016)
Background: The effect of probiotic bacteria (Lactobacillus acidophilus and L. casei) as safe organisms was examined on fungal growth and aflatoxin gene regulation in Aspergillus parasiticus. Methods: The fungus was cultured in presence of two different concentrations of L. acidophilus and L. casei in MRS broth medium. Mycelia dry weight is indicated as criteria to evaluate fungal growth. Besides, investigation of aflR gene expression by Real Time PCR was performed for analysis of gene regulatory effects in aflatoxin biosynthetic pathway. Results: Both Lactobacillus strongly inhibited fungal growth in the concentrations of 1. 5 102, 1. 5 103 . Expression analysis of aflatoxin genes pathway by real time PCR showed inhibitory effect of L. acidophilus and L. casei on expression of aflR gene. The gene expression revealed to be reduced at the approximate rates of 99. 7% and 98% respectively by L. acidopholus and L. casei in concentrations of 1. 5 102  and more. Conclusion: L. acidophilus and L. casei may be used successfully as suitable candidates in controlling of A. parasiticus growth on food and feed as well as reducing of aflatoxin contamination. Keywords: Aflatoxin, Aspergillus parasiticus, Lactobacilus acidophilus, Lactobacilus casei,